2015
DOI: 10.1007/s11356-015-5791-x
|View full text |Cite
|
Sign up to set email alerts
|

Hospital admissions due to diseases of arteries and veins peaked at physiological equivalent temperature −10 to 10 °C in Germany in 2009–2011

Abstract: We aimed to understand relationships of the weather as biometeorological and hospital admissions due to diseases of arteries and veins by subtypes, which have been scarcely studied, in a national setting in recent years. This is an ecological study. Ten percent of daily hospital admissions from the included hospitals (n = 1,618) across Germany that were available between 1 January 2009 and 31 December 2011 (n = 5,235,600) were extracted from Statistisches Bundesamt, Germany. We identified I70-I79 Diseases of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…A total of 106 among the 129 studies were excluded for the reasons as follows: five studies 1519 failed to provide data aggregated on monthly and seasonal retrieval, seven reported insufficient data, 15 were commentary literature or reviews, and 55 cannot meet the inclusion criteria. Finally, it was identified that 23 eligible studies 79,2039 met the inclusion criteria of the meta-analysis, including 40,309 patients with VTE including PE, DVT, or SVT. Figure 1 summarizes the selection flow and inclusion process of the study.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 106 among the 129 studies were excluded for the reasons as follows: five studies 1519 failed to provide data aggregated on monthly and seasonal retrieval, seven reported insufficient data, 15 were commentary literature or reviews, and 55 cannot meet the inclusion criteria. Finally, it was identified that 23 eligible studies 79,2039 met the inclusion criteria of the meta-analysis, including 40,309 patients with VTE including PE, DVT, or SVT. Figure 1 summarizes the selection flow and inclusion process of the study.…”
Section: Resultsmentioning
confidence: 99%
“…The basic information required for the extraction of the meta-analysis is shown in Table 1 (Ref. [17,[20][21][22][23][24][25][29][30][31][32][33][34][35][36][37][38][39][40][41][42]).…”
Section: Literature Selection Process and Resultsmentioning
confidence: 99%